Influenza vaccination in children at high risk of respiratory disease. (May 2013) - Patria, Maria Francesca; Tagliabue, Claudia; Longhi, Benedetta; Esposito, Susanna
Chronic respiratory diseases (CRDs) are a heterogeneous group of diseases that can affect the pediatric population and health authorities throughout the world recommend influenza vaccination because of the significant risk of influenza-related complications. However, despite this recommendation, vaccine coverage is generally unsatisfactory. The aim of this review is to analyze the impact of influenza on children at high risk of respiratory disease, and the immunogenicity, safety and efficacy of influenza vaccination in such children. The results show that there is a significant risk of influenza-related complications in preterm neonates and infants, in whom influenza vaccines are immunogenic and safe (although their efficacy has not been specifically studied). There are conflicting data concerning the effect of influenza infection on asthma morbidity in children, and whether or not influenza vaccination helps to prevent asthma exacerbations. Recent data provide no evidence that influenza is more frequent in patients with cystic fibrosis than in healthy subjects, or that it is responsible for increased lower respiratory tract morbidity. The lack of any clear correlate of protection suggests that future studies should also consider the efficacy of the different influenza vaccines and not only evaluate them in terms of immunogenicity. Furthermore, there is a need for clinical studies to assess the effectiveness of the available vaccines in patients with other rare CRDs and other chronic underlying diseases with possibly severe respiratory involvement. It is also important to determine whether children with recurrent respiratory tract infections should be included in the list of those for whom influenza vaccination is recommended. In the meantime, given the increasing evidence of the burden of influenza on the population as a whole and the benefits associated with vaccination, annual influenza vaccinations should be recommended for all children at high risk of respiratory disease and the members of their households.